2016
DOI: 10.1093/treephys/tpv140
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of light-dependent regulation of state transitions in gymnosperms

Abstract: The goal of this study was to characterize the light-dependent regulation of state transitions in gymnosperms. Two species of conifer were examined: eastern white pine (Pinus strobus L.) and white spruce [Picea glauca (Moench) Voss], as well as the angiosperm pumpkin (Cucurbita pepo L. subsp. pepo). Both diurnal time courses in the field and manipulated light experiments in growth chambers were conducted. Results from chlorophyll fluorescence analysis indicated that pumpkin was able to use a larger fraction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…6 ). The destacking and linearization of thylakoids upon formation of 3p-LHCII could, in turn, lead to loosening of the lateral heterogeneity of photosystems and thereby increase the chance for PSII–PSI spillover, which has been suggested to be involved in sustained NPQ ( 1 , 17 , 46 ). Conversely, a coherent restoration of Fv/Fm and dephosphorylation of 3p-LHCII occurred upon recovery of spruce needles from sustained NPQ ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6 ). The destacking and linearization of thylakoids upon formation of 3p-LHCII could, in turn, lead to loosening of the lateral heterogeneity of photosystems and thereby increase the chance for PSII–PSI spillover, which has been suggested to be involved in sustained NPQ ( 1 , 17 , 46 ). Conversely, a coherent restoration of Fv/Fm and dephosphorylation of 3p-LHCII occurred upon recovery of spruce needles from sustained NPQ ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, the Pinus and Picea species, both lacking Lhcb3 and CP24, might be interesting models to study the effect of these proteins on state transitions in plants. To our knowledge, this regulation mechanism has been little studied in gymnosperms so far, although recent studies found a relatively high phosphorylation of LHCII in high light in conifers compared to angiosperms [107,108], suggesting a different regulation of energy dissipation and possibly also of state transitions. It is nonetheless possible that the absence of Lhcb3 in pine species facilitates this higher phosphorylation.…”
Section: State Transitions: the Impact Of Lhcii Evolution On A Widespmentioning
confidence: 98%